Schizophrenia Reflected in Jeff Nichols’s Take Shelter (2011) - Ihwan Qorib (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2021)
This study is aimed to analyze : (1) the symptoms of schizophrenia in Jeff Nichols’s “Take Shelter” (2) the psychological condition of Curtis as schizophrenic reflected in Jeff Nichols’s “Take Shelter”.The study uses descriptive qualitative method to analyzed the film entitle “Take Shelter” directed by Jeff Nichols as the objective of the research. The method of collecting data includes watching and reading, identifying, classifying, and selecting. The method of analyzing the data by displaying, explaining, and interpreting. The data analyzed by using Abnormal psychology and Sigmund Freud Psychoanalysis.The result of the study : (1) the symptoms of schizophrenia reflected in Jeff Nichols’s Take Shelter such as hallucination, delusion, disorganized behaviour, and several negative symptoms; (2) the psychological condition of Curtis as schizophrenic in form of feeling anxious due to the hallucination and delusion, disorganized behaviour, and stress and analyzed by using Sigmund Freud psychoanalysis.